2021
DOI: 10.3389/fpubh.2021.697826
|View full text |Cite
|
Sign up to set email alerts
|

Can Health Human Capital Help the Sub-Saharan Africa Out of the Poverty Trap? An ARDL Model Approach

Abstract: This article explores the impact of health human capital on the poverty trap in Sub-Saharan Africa by autoregressive distribution lag model. In the long run, there is no evidence that health human capital can help the Sahara out of the poverty trap. While health human capital has a significant effect on poverty reduction in the short term. There is a threshold effect in the poverty reduction model of healthy human capital. When the economic development level reaches the threshold, the effect of poverty reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Based on the panel data of 65 generic drug-listed companies in China from 2011 to 2020, this paper uses the double-difference method to evaluate the impact of drug centralized procurement policy of China on the net profit of enterprises and draws the following conclusions: first, before the implementation of the policy, the difference between successful enterprises and unsuccessful enterprises is not obvious. After the implementation of the policy, the net profit of the winning enterprise decreased significantly ( 25 , 56 58 ). Therefore, centralized drug procurement policy of China is not conducive to the improvement of enterprise net profit in the short term, and the effect is more obvious with the increase of policy implementation years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the panel data of 65 generic drug-listed companies in China from 2011 to 2020, this paper uses the double-difference method to evaluate the impact of drug centralized procurement policy of China on the net profit of enterprises and draws the following conclusions: first, before the implementation of the policy, the difference between successful enterprises and unsuccessful enterprises is not obvious. After the implementation of the policy, the net profit of the winning enterprise decreased significantly ( 25 , 56 58 ). Therefore, centralized drug procurement policy of China is not conducive to the improvement of enterprise net profit in the short term, and the effect is more obvious with the increase of policy implementation years.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, there are three different views: one is that government centralized purchase promotes the growth of enterprise net profit through internal incentives ( 22 , 23 ). The other believes that due to information asymmetry, government intervention has an inhibitory effect on enterprise net profit ( 24 , 25 ). In addition, some scholars believe that the impact of centralized government drug procurement on the net profit of enterprises is uncertain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Good health is also identified as one of the essential factors that can make economic growth possible in Sub-Saharan Africa (Ogundari and Awokuse 2018 ). Promoting national health insurance and strengthening the health system has emerged as a solution “to get rid of the poverty trap” in the Sub-Saharan region (Wang et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the Sub-Saharan Africa region, a recent study has found that “to get rid of the poverty trap in this region, the government needs to promote the national health insurance and strengthen the health system as a whole plan” (Wang et al 2021 ). According to Ifeagwu et al ( 2021 ), 27 out of 48 countries in Sub-Saharan Africa are affected by direct out-of-pocket payments for healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…6 Furthermore, the Jarque-Bera index indicates that OP, NEVs, and AQ are significantly nonnormally distributed at the 1% level. 65,66 The empirical analysis uses the natural logarithm of the variables.…”
Section: Datamentioning
confidence: 99%